On Performance Criticism, Lived Religion, and the Hebrew Bible - Thompson, Shane M. (Currents in biblical research, 2024)
This article provides an overview of the application of a performance criticism framework within scholarship on the Hebrew Bible. A natural progression from conversations concerning orality, performance studies allows for increased explication of the biblical texts, most notably pertaining to life, religion, and culture in ancient Israel. The addition of ‘lived religion’ through a performance studies lens advances the understanding of peoples and areas of life commonly deemed absent from the biblical record. Instead, they are present in the form of an audience witnessing or hearing the performances of, or contained within, these texts.